A new mountain pitviper of the genus Ovophis Burger in Hoge & Romano-Hoge, 1981 (Serpentes, Viperidae) from Yunnan, China - Qiu, Xian-Chun; Wang, Jin-Ze; Xia, Zu-Yao; Jiang, Zhong-Wen; Zeng, Yan; Wang, Nan; Li, Pi-Peng; Shi, Jing-Song (ZooKeys, 2024)
Based on a molecular phylogenetic analysis and morphological comparison, a new species of mountain pitviper, Ovophis jenkinsi sp. nov. , is described. The new species was collected in Yingjiang County, Yunnan Province, China. It can be distinguished from congeneric species by the following characters: (1) internasals in contact or separated by one small scale; (2) second supralabial entire and bordering the loreal pit; (3) dorsal scales in 23 (25)–21 (23, 25)–19 (17, 21) rows; (4) 134–142 ventrals; (5) 40–52 pairs of subcaudals; (6) third supralabial larger than fourth in all examined specimens of Ovophis jenkinsi sp. nov. ; (7) deep orange-brown or dark brownish-grey markings on dorsal head surface; (8) background color of dorsal surface deep orange-brown or dark brownish-grey; (9) both sides of dorsum display dark brown trapezoidal patches; (10) scattered small white spots on dorsal surface of tail.